2006
DOI: 10.1111/j.1439-0523.2006.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of genomic DNA sequences of the S‐ribonuclease gene associated with self‐incompatibility allelesS1toS5in European pear

Abstract: The stylar products of the S-locus for the gametophytic self-incompatibility (GSI) system in the Rosaceae are ribonucleases (S-RNases). Recently, sequences for 13 pear S-RNase alleles have been published and named following a letter-symbol nomenclature (S a to S d and S h to S p ). To establish the correspondence between these sequences and the self-incompatibility alleles we have described previously (S 1 to S 5 ), we have amplified genomic DNA with consensus primers from the cultivars, ÔWilliamsÕ (S 1 S 2 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Sequence identities between new and previously reported alleles varied between 59% (S 14 vs. S 20 ) and 93% (S 5 vs. S 23 ). These values fit within the range of variation (59-92%) observed for S 1 through S 14 , the S-RNases found associated with 14 Salleles as determined by pollination experiments (Sanzol et al 2006;Sanzol and Robbins 2008). Together, these results suggested that the genomic regions characterized in this study correspond to the S-RNases of new S-alleles of European pear.…”
Section: Genomic Characterization Of S-rnases In European Pear Cultivarssupporting
confidence: 76%
See 4 more Smart Citations
“…Sequence identities between new and previously reported alleles varied between 59% (S 14 vs. S 20 ) and 93% (S 5 vs. S 23 ). These values fit within the range of variation (59-92%) observed for S 1 through S 14 , the S-RNases found associated with 14 Salleles as determined by pollination experiments (Sanzol et al 2006;Sanzol and Robbins 2008). Together, these results suggested that the genomic regions characterized in this study correspond to the S-RNases of new S-alleles of European pear.…”
Section: Genomic Characterization Of S-rnases In European Pear Cultivarssupporting
confidence: 76%
“…The new S-RNases have all the structural features expected for the Maloideae S-RNase, including the conserved and variable regions, and several residues important for the secondary structure and activity of the protein (Ishimizu et al 1996(Ishimizu et al , 1998. Additionally, sequence identities between the new alleles and previously reported S-RNases varied within the same range calculated for S 1 through S 14 , which have distinct recognition specificities (Sanzol et al 2006;Sanzol and Robbins 2008). Pollination tests confirmed that cultivars bearing S 20 or S 21 and having the same S-genotype were cross-incompatible.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations